1997
DOI: 10.1002/(sici)1097-0142(19971001)80:7<1228::aid-cncr5>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein overexpression is common and independent of human papillomavirus infection in squamous cell carcinoma of the vulva

Abstract: METHODS.Immunohistochemical methods for the detection of p53 protein and consensus primer polymerase chain reaction (PCR) were used, followed by direct 1 Department of Gynecology, Leiden University sequencing of the PCR product for the evaluation of HPV subtype infection. SixtyMedical Centre, The Hague, The Netherlands.six patients with squamous cell carcinoma of the vulva were available for this study. pending on the method of detection and the carcinoma subtype.5-8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 34 publications
2
48
0
2
Order By: Relevance
“…p53 may be involved in progression from VIN to VSCC as p53 product accumulated in 53% of VSCCs (n ϭ 66) 13 and 44% (n ϭ 34) 14 of VIN associated with VSCC, but 0% of VIN not associated with VSCC (n ϭ 28). 4 In our series, the p53 locus was lost more in VSCC(ϩ) than in VIN(ϩ), which in turn had more loss of p53 than VIN(Ϫ) (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…p53 may be involved in progression from VIN to VSCC as p53 product accumulated in 53% of VSCCs (n ϭ 66) 13 and 44% (n ϭ 34) 14 of VIN associated with VSCC, but 0% of VIN not associated with VSCC (n ϭ 28). 4 In our series, the p53 locus was lost more in VSCC(ϩ) than in VIN(ϩ), which in turn had more loss of p53 than VIN(Ϫ) (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The loci studied were chosen for specific reasons: 17p13 because it harbors p53, which accumulates in 53-68% of VSCC 13,14 and 9p21 (p16 gene) and 3p25 because they frequently exhibit LOH in squamous head and neck cancer. [15][16][17] p16 is also disrupted in VIN and VSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, p53 mutation frequency in vulvar carcinomas is reported to be much higher compared with cervical carcinoma by 24%, (Lee et al, 1994), 53% (Milde-Langosch et al, 1995) and Elderly Japanese women with cervical carcinoma show higher proportions of both intermediate-risk human papillomavirus types and p53 mutations 53% (Kagie et al, 1997). Vulvar cancer generally occurs in women over ten years older than women with cervical cancer, with a peak incidence between 65 and 75 years old (Langosch et al, 1995).…”
mentioning
confidence: 99%
“…Neither have we found a relation between p53 and clinicopathological parameters age, depth of invasion and differentiation grade. In their study of vulvar carcinomas, Kagie et al (1997) did not find a relationship between p53 overexpression and diseasefree survival. Kohlberger et al (1995) have reported a relationship between p53 overexpression and survival in vulvar carcinomas, based on a group of 25 vulvar carcinomas.…”
Section: Discussionmentioning
confidence: 99%